The labour market for the port of the future. A case study for the port of Antwerp. Issue 2 (June 2020) - Esser, Anton; Sys, Christa; Vanelslander, Thierry; Verhetsel, Ann
Graphical abstract: Highlights: The impact of information technology on the job market in ports is disruptive. The port of Antwerp faces challenges regarding employment, skills and competences. The future port job market is polarized as midfield administrative staff will disappear. Next to sector-specific knowledge, soft skills should be implemented in education. The growing complexity of processes in ports requires high level training programmes. Special attention is needed to motivate and accept females in the port job market. Abstract: Major changes in the job market are currently observed, among others a consequence of the introduction of information and communication technology (ICT) in port areas. The question is how important the mismatch is between supply and demand for jobs, skills and competences, as a consequence among others of the above-mentioned changes. From literature, general trends in the job market are identified and their impact is translated to new trends in ports. The aim of the research is threefold: mapping the eventual mismatch in terms of employment, examining whether technological innovations (ICT and automation) have an impact on the future professions and specialisations and identifying the skills that need to be developed by education. The case is the maritime and non-maritime cluster in the port of Antwerp looking forward at a 2030 horizon. Next to conducting a literature review, the study analyses quantitative data on the characteristics of employment in the port of Antwerp provided by the social security administration. Moreover a qualitative analysis through interviews was done in close cooperation with the port community, including port companies, port associations and educational institutes. The main results are threefold. First, the appearance of a polarised job market, where due to ICT introduction and automation, a lot of middle-paid paperwork jobs disappear. Second, that jobs on the floor will be more and more assisted by robotics and data applications and analysis, including use of machine learning and artificial intelligence. Third, that management jobs will become more and more complex with multi-skilling becoming a key. Therefore training programmes must include new skills like ICT, but also soft skills like teamwork and communication. Special attention is needed to motivate and host females and non-natives in the port job market.